From Academic Entrepreneurship to Regional Development: A Literature Review of the Impact Pathways of University Innovation Ecosystems - Patricia, Mia Christy; Yulianti, Grace (LPPM STIE Kasih Bangsa, 2026)
This qualitative literature review examines the impact pathways of University Innovation and Entrepreneurial Ecosystems (UIEEs) on regional development. Synthesizing findings from recent empirical and conceptual studies, the review identifies key mechanisms such as academic entrepreneurship, university–industry collaboration, policy integration, and human capital formation. The analysis highlights the evolving role of universities as ecosystem orchestrators that drive not only innovation and economic growth but also social inclusion and sustainability. While contextual differences shape outcomes, best practices emphasize multilevel governance, stakeholder engagement, and place-based strategies. The study contributes to a deeper understanding of UIEEs as complex, adaptive systems and calls for more longitudinal and regionally diverse research to support future policymaking and institutional design